An audit of cancellation of elective surgery in paediatric patients at Chris Hani Baragwanath Academic Hospital - Gamede, Nomdumiso (My University, 2024)
Background: Cancellation of elective surgery is one of the quality indicators of theatre operation worldwide. The cancellation of elective surgery in paediatric patients is a world-wide problem with the rates ranging from 0.21% to 44%. This study aimed to determine the rates and describe the reasons for cancellation of elective surgeries in paediatric patients at Chris Hani Baragwanath Academic Hospital (CHBAH). Methods: A retrospective study was conducted using theatre records from 01 January to 31 December 2019. The numbers and reasons for elective paediatric surgeries were reviewed. Data was collected using structured collection sheet and entered into Microsoft excel. Statistical Package for Social Sciences was also used to further analyse the data. Results were expressed as percentages in a graph and table forms. Results: In the year 2019, a total of 3399 elective paediatric procedures were scheduled in fourteen specialties at CHBAH. Of these, 634 (19%) were cancelled due to various reasons. The highest number of cases cancelled were from paediatric surgery and neonates (n=204, 31%), followed by ENT (n=99, 24%), burns (n=80, 20%) and paediatric orthopaedics (n=79, 16%). The lowest number of cancelled cases came from urology (n=3, 17%) and hands (n=3, 3%). The commonest reason for cancellation of elective surgery in paediatric patients at CHBAH was found to be time constraint (34%) followed by patients not arriving for surgery (16%). The reasons for cancellation in our study were mostly due to avoidable factors at 68% and non-avoidable at 32%. Conclusion: The rate of cancellation in our study was high but comparable to other African and South African studies. Majority of the causes for cancellation were avoidable.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Medicine (MMed) in Anaesthesiology to the Faculty of Health Sciences, University of the Witwatersrand, School of Clinical Medicine, Johannesburg, 2023
Keywords: Elective surgery; Paediatric patients; SDG-3: Good health and well-being; SDG-16: Peace, justice and strong institutions